The Influence of Digital Marketing and Social Media Marketing on Purchase Intention with Brand Awareness as Mediator - Nanang Adie Setyawan; Bagus Yunianto Wibowo; Destine Fajar Wiedayanti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Driven by the burgeoning influence of digital marketing and social media marketing on consumer behavior within the Indonesian restaurant sector, this study investigates their effect on purchase intention. The primary objective is to evaluate how these digital strategies affect consumer intent, both directly and through the mediating role of brand awareness. Utilizing a quantitative methodology and a cross-sectional survey design, the research gathered data from 200 patrons of prominent restaurants in Semarang City. The subsequent analysis was performed using Structural Equation Modeling (SEM) via IBM AMOS 24 software. The empirical results demonstrate that both digital marketing and social media marketing exert positive and significant effects on brand awareness and purchase intention, with social media marketing exhibiting a more pronounced influence. Additionally, brand awareness was found to significantly enhance purchase intention while functioning as a critical mediator between marketing efforts and consumer decisions. The study concludes that optimizing digital strategies, especially on social media, is vital for elevating brand visibility and stimulating consumer interest. These findings underscore the necessity for restaurant operators to craft interactive and pertinent digital content to maintain a competitive advantage in the modern digital marketplace.